CASE REPORT: MANUAL REPOSITIONING MANAGEMENT OF UTERINE PROLAPSE IN CATTLE AT SMALLHOLDER FARMS IN LIMAPULUH KOTA REGENCY - Anna Zukiaturrahmah; Ulfa Rahmi Putri; Darwis; Usma Aulia; Juliadi Ramadhan; Sri Rezeki (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
Uterine prolapse is a reproductive disorder in cattle that requires prompt and effective management to ensure survival, recovery, and preservation of fertility. Uterine prolapse is defined as the protrusion of the uterus through the vulva, exposing the mucosal surface. This case report describes the occurrence of uterine prolapse in a cow and its therapeutic management. Clinical examination revealed that the uterus was protruding outside the pelvic cavity, accompanied by weakness and anorexia. The patient was diagnosed with a uterine prolapse. The treatment consisted of manual uterine repositioning, followed by vulvar suturing. Supportive therapy, including antibiotics, multivitamins, calcium supplementation, and topical antiseptics, was administered for seven days. The cow showed favorable recovery and complete resolution of the uterine prolapse. The prevention of recurrent uterine prolapse in cattle includes adequate uterine repositioning, temporary vulvar suturing, correction of postpartum metabolic disorders, appropriate nutritional management, and close postpartum monitoring.